(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Phulkari embroidery is a uniquely vibrant and intricate craft hailing from the Punjab region of India and Pakistan. This research paper delves into the techniques and stitches employed in traditional phulkari embroidery, shedding light on the rich heritage, cultural significance, and artistic brilliance of this time-honored craft. Through the examination of historical records, interviews with artisans, and analysis of existing phulkari works, the paper aims to present a comprehensive overview of the different stitches and techniques used in phulkari embroidery, along with their applications and regional variations.